Analisis Manajemen Risiko Pada UMKM Kupat Tahu - Khoeri, Musodik; Syahanra, Ardiva Zuniar (Universitas Serambi Mekkah, 2024)
This study examines the entrepreneurial strategies and challenges faced by traditional tofu and kupat tahu (Indonesian-style tofu and fermented soybean cake) micro-businesses in Indonesia. A qualitative approach was employed, involving in-depth interviews with 20 UMKM (Usaha Mikro, Kecil, dan Menengah) owners. Findings indicate that product quality, pricing, and innovative marketing strategies are crucial for competitiveness. However, challenges persist, including limited access to financing, regulatory compliance, and market fluctuations. The research implications highlight the need for targeted government support and training programs to enhance the resilience and sustainability of UMKM in the Indonesian food industry.